NGOs: Activities on Combating Trafficking in Human Beings and Challenges at Work - K. B. Levchenko; O. V. Shved (Bulletin of Kharkiv National University of Internal Affairs)
Combating trafficking in human beings is a major challenge for society and constitutes a separate policy area, where the subjects of its implementation are both governmental and non-governmental organizations. The role of the latter is multifaceted and subject to change and development. The author of the article has studied the development of forms and directions of activity of organizations, their interaction with various state institutions, scientific and educational institutions to ensure their effective development. The methodological basis of the publication was a dialectical approach to the cognition of social and legal phenomena through the historical and comparative legal analysis of definitions, the use of the method of included observation, as well as problem-chronological analysis of the activities and participation of public organizations in the formation and implementation of state policy. Theoretical basis of the publication was theoretical and ideological concepts and research of domestic and foreign scholars in relation to public organizations. The scientific novelty of the article is to cover the dynamics of the development of public organizations’ participation in the process of forming and implementing state policy on the example of combating trafficking in human beings, as well as in analyzing the interaction of public organizations with educational and scientific institutions as a factor of ensuring the qualitative and effective work of both parties. The author has distinguished and analyzed three stages in the formation and development of NGOs working in the field of combating trafficking in human beings: the first – the nineties of the XX century, the second – 2000–2013, the third – from 2014 to the present day. In order to effectively develop NGOs, it is important to interact with educational and scientific institutions, to share experience and knowledge. Positive changes can be caused by prudent implementation of necessary policies, continuous improvement of the professional level of the employees, transparency in the activities of NGOs, providing feedback to their target groups, a combination of professionalism and activism, cooperation with state institutions.